Studies of the Reproductive Biology of Toona ciliata M. Roem under the Himachal Pradesh Condition - Singh, Thiyam Jefferson; Gupta, Tara (International Journal of Bio-resource and Stress Management, 2017)
Toona ciliata is an important timber species of India which is found in H.P. as natural populations, mostly along the cultivated fields and roads. The present studies on various facets of reproductive biology were conducted under the Dept. of Tree Improvement and Genetic Resources during 2011 in which three sites namely Jaunaji, Dharja and Kandaghat with elevations 1400 m, 1215 m and 1180 m respectively in district Solan. The studies included full coverage of phenophases as a physiological basis of reproductive growth. The phenological studies included the morphological characters such as leafing, flowering and fruiting in which leaf bud appearance was first observed in L2 (Dharja) followed by L1 (Jaunaji) and L3 (Kandaghat). Fruit development at first instance was recorded in L1 (Jaunaji), L2 (Dharja) and the lastly from L3 (Kandaghat). The floral morphology was also one of the parameter in which the type of inflorescence was observed to be consisting of numerous flowers born in thyrse bearing paniculate racemes at the apex of the branchlets bearing compound leaves. The flowers are functionally unisexual but morphologically bisexual. Calyx is polysepalous. Corolla was found to have five equal sized petals which were longer than the calyx and adnate near the base. Anthesis of flowers was observed to take place between 7.00 a.m. to 1.00 p.m. for all the three localities. The mode of pollination was observed to be both cross and self pollination but tends to be out crossed.The pollen grains exhibited a light creamish colour. Pollinators were found to be thrips and bees.